The effects of opportunities and founder experience on new firm performance - Dencker, John C.; Gruber, Marc (Strategic Management Journal, 2015)
Much prior research in entrepreneurship has focused on the role of the founder's knowledge in affecting new firm performance. Yet, little is known about how and why the entrepreneurial opportunity itself shapes outcomes in this arena. We begin filling in this critical gap in the literature by examining how the riskiness of the opportunity not only affects start‐up performance, but also conditions the relevance of the founder's distinct knowledge endowments. Analyses of a sample of 451 new firms show that the riskier the opportunity, the greater the performance of the start‐up, above and beyond founder characteristics. Moreover, the value of founder knowledge is relative to the type of opportunity exploited: high‐risk opportunities favor founders with managerial experience, whereas low‐risk opportunities favor founders with industry experience . Copyright © 2014 John Wiley & Sons, Ltd.